Health Analysis Based on the Technical Guideline of the Cooperative Deputy No. 15 of 2021 - Kristanto Kristanto; Lely Ana Ferawati Ekaningsih Ekaningsih (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study aims to analyze the health level of Koperasi AUSATH Blokagung, Tegalsari, Banyuwangi. Employing a quantitative explanatory approach, the research focuses on four key dimensions: governance, risk profile, financial performance, and capital structure. The dataset consists of primary data obtained through interviews and secondary data derived from the cooperative’s 2024 financial statements. Data collection techniques include observation, interviews, and documentation, while the analysis follows the Technical Guidelines of the Deputy for Cooperatives No. 15 of 2021 concerning the Cooperative Health Examination Worksheet (KKPKK). The findings across the four dimensions indicate that the cooperative is in a healthy condition. The management system operates effectively with sound governance and regulatory compliance, supported by strong liquidity, stable financial performance, optimal profitability, and efficient operations. The capital structure is also robust, providing a solid financial and managerial foundation for sustainable growth. Overall, Koperasi AUSATH meets the cooperative health standards stipulated in the Deputy’s Technical Guidelines and demonstrates its capacity to function as a financial intermediary within the community. Furthermore, this compliance reflects alignment with Islamic principles, as emphasized in the Qur’an: Surah Al-Baqarah verse 2 on the prohibition of usury (riba), Surah Al-Maidah verse 2 on mutual assistance in goodness, and Surah Sad verse 24 on cooperation and solidarity Keywords : Risk Profile, Governance, Health, Cooperatives, and Financial Performance